Hepatitis C in Children Co-infected With Human Immunodeficiency Virus. Issue 4 (October 2015) - Indolfi, Giuseppe; Bartolini, Elisa; Serranti, Daniele; Azzari, Chiara; Resti, Massimo
ABSTRACT: Objectives: The objective of this systematic review was to summarize evidence regarding hepatitis C in hepatitis C virus/human immunodeficiency virus (HCV/HIV)–co-infected children focusing on mother-to-child transmission, clinical and laboratory features, outcome, and therapies. Methods: A literature search was performed using multiple keywords and standardized terminology in MEDLINE, EMBASE, and Cochrane databases dating back to their inception up to April 1, 2015, using the following terms hepatitis C virus, HIV, and child. Results: Fifty-five of 367 publications were selected for inclusion. In co-infected children, HIV impacted all the different aspects of HCV infection. Maternal HIV infection increased the risk of vertical transmission of hepatitis C. Children with HCV/HIV co-infection presented a lower rate of spontaneous clearance of HCV, were more commonly HCV viraemic, and had higher values of alanine aminotransferase when compared with HCV-monoinfected children. No relevant difference was reported between monoinfection and co-infection with regard to clinical findings. Although the data on the outcome of hepatitis C in the context of co-infection were limited, they were highly suggestive of a more severe outcome in terms of fibrosis in co-infected children. No pediatric data were available on the role of antiretroviral therapy as a cofactor of liver injury in HCV/HIV co-infection. The efficacy of pegylated interferon-α and ribavirin in children with HCV/HIV co-infection was lower than in monoinfected children. Conclusions: The effect of HIV co-infection on HCV-related disease was clear with most studies indicating that HIV accelerates HCV progression and reduces the efficacy of the available anti-HCV therapies. Abstract : Supplemental Digital Content is available in the text